"Let us create space": Reclaiming peace and security in a Kenyan Somali community. (October 2021) - Feghali, Sylvia; Faria, Caroline; Jama, Fardowsa
Abstract: This article pushes for a postcolonial, feminist critique of "anti-terrorist" securitization, that makes space for transformative peace-building. The post-9/11 securitization of the African continent builds on a long legacy of colonial conquest and racist Othering. Somalia is regularly centered here, portrayed in media and state narratives as a volatile failed state, one that produces terrorist bodies and acts. But rather than building peace, we follow others in arguing that the projects of securitization have stoked violence, intensifying discrimination against the Somali diasporic community (Mohamed, 2017; Wairuri, 2020). To counter this dominant narrative, we centre the Somali-Kenyan Awjama Cultural Centre, in the Eastleigh neighborhood of Nairobi, Kenya. A particularly rich and instructive case study of peace-making through community activism, we ask: How do Somalis who use the Centre subvert racist, Islamophobic narratives and reclaim their own modes of representation? And how do these new narratives disrupt systemic violence and build peace? Demonstrating the insights of a feminist, postcolonial geographic approach, we argue that spaces like the Awjama Centre provide interpersonal support and new kinds of (self-) representation. These fundamentally disrupt single stories of Africa and of terrorism, with greater possibilities for establishing long-term embodied peace than projects of geopolitical securitization.